PENGARUH PERTUMBUHAN PENJUALAN, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - Isa Rusianti; Ika Wahyuni; Ida Subaida (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
This research used observation, literature study, and documentation as the methods. The data were analysed by using classical assumption test, multiple linear regression analysis, hypothesis test, dominant test, and coefficient of determination. The statistical test of the results of the regression variable X1 Sales growth has a positive effect on the variable capital structure Y, while the variables X2 Profitability and X3 Company size have a negative effect on the variable capital structure Y. This is shown in the results of multiple linear regression analysis, namely Y = 2,906 + 0.019 X1 - 5,307X2 - 0,059X3 + e. Partially the variable X1 Sales growth tcount 0,323 has no partial effect on the variable Capital structure Y, X2 Profitability tcount -3.942 has a partial effect on the variable Capital structure Y, while X3 Firm size tcount -1, 0323 has no partial effect on the variable Capital structure Y Simultaneously X1 Sales growth, X2 Profitability, X3 Firm size has a significant effect on the capital structure variable Y because Fcount 7,394> Ftable 2,90. The dominant test of this research is the variable X2 Profitability of -3.942, which is greater than the value of X1 Sales growth of 0.323 and X3 Company size of -1.306. The coefficient of determination test (R2) obtained the result of 0.409. that means that the influence of the variable Sales growth, Profitability, and company size has a contribution of 40.90% to the variable Y capital structure. According to the standard interpretation, the effect is quite significant. The remaining 59.10% is influenced by other factors not discussed in the study.